2014
DOI: 10.1038/srep06994
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of metastatic and angiogenic potency of malignant cancer by Eupatorium fortunei via suppression of MMP-9 activity and VEGF production

Abstract: Eupatorium fortunei has long been used to treat nausea and poor appetite, and has been prescribed as a diuretic and detoxifying drug in Chinese medicine. Recent studies have demonstrated that E. fortunei possesses anti-bacterial, anti-oxidant, and anti-diabetic activities, as well as cytotoxicity to human leukemia cells. However, at non-toxic concentrations, the effects of an aqueous extract of E. fortunei (WEF) on the metastatic and angiogenic potential of malignant tumor cells have not been reported. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 41 publications
(54 reference statements)
3
29
0
Order By: Relevance
“…As reported previously4445, CM from HT1080 cells dramatically promoted migration across Transwells and tube-like network formation on the Matrigel of HUVECs and increased the sprouting of microvessels from aortic rings; CM from ELH-treated HT1080 cells induced these changes to a lesser extent and caused no cytotoxicity (Fig. 6A–C).…”
Section: Discussionsupporting
confidence: 85%
“…As reported previously4445, CM from HT1080 cells dramatically promoted migration across Transwells and tube-like network formation on the Matrigel of HUVECs and increased the sprouting of microvessels from aortic rings; CM from ELH-treated HT1080 cells induced these changes to a lesser extent and caused no cytotoxicity (Fig. 6A–C).…”
Section: Discussionsupporting
confidence: 85%
“…HIF1a allows cells to overcome hypoxic conditions, which are common in the core of tumors and for metastases that may not have an established blood supply. Furthermore, through its transcriptional activation of VEGF, HIF1a promotes angiogenesis, and therefore oxygen supply for metastatic sites (Lin et al, 2004;Liang et al, 2008;Kim et al, 2014). The novel function of the sigma-2 receptor that our study has revealed is consistent with this role of HIF1a in rapidly proliferating cancer cells and allows for congruous explanation of the high expression of sigma-2 receptors in the same.…”
Section: Activation Of Sigma-2 Receptor Induces Metabolic Stimulationsupporting
confidence: 77%
“…Abnormal secretion of HA has been observed in malignant tumors (18), however, HA is required in normal tissue, therefore, it is important to clarify the regulating system for HA secretion. Kim et al (19) have reported that suppression of MMP-9 activity and vascular endothelial growth factor production in malignant tumor cells reduces tumor metastasis and angiogenic potency. In addition, Rauhala et al (20) have demonstrated that keratinocytes exposed to low-dose UVB radiation increased HA synthesis with the production of ROS.…”
Section: Discussionmentioning
confidence: 99%